THE DEPLOYMENT OF BIODIGESTER SYSTEMS IN RURAL PROPERTIES - HALMEMAN, M.C.R.; STACHISSINI, M.G.; DAMACENO, F.M.; GABRIEL FILHO, L.R.A.; CREMASCO, C.P.; PUTTI, F.F. (Revista Brasileira de Engenharia de Biossistemas, 2014)
Swine production has a strong impact on the national and international meat economy. However, this type of agribusiness generates solid and liquid wastes which impact the environment when deposited inadequately. An alternative for the treatment of these effluents would combine appropriate management of residual biomass to the digester system. Current study collects data to deploy a digester system on a rural property in Mambore PR Brazil, with a herd of 330 matrices. Further, 30,301.49 kg.day-1 in feces and urine and use of 15,673 m3 of water were obtained. Daily volume of wastes estimated the amount of biogas within conditions of hydraulic retention time (HRT) of 22 days and 30 days, with temperature variation of biomass at 20°C, 25°C and 30°C. Electric energy produced was estimated at105,553.95 kWh.year-1 with HRT of 22 days and 20°C. Under the above conditions, the biofertilizer produced amounted to 27,500 kg. Thus, the biogas produced could generate electricity to meet the needs of the farm and the bio-fertilizer produced could be used on crops or sold.